2020
DOI: 10.1302/1863-2548.14.200065
|View full text |Cite
|
Sign up to set email alerts
|

Is acetabular dysplasia and pelvic deformity properly interpreted in patients with congenital femoral deficiency? A 3D analysis of pelvic computed tomography

Abstract: Purpose The aim of this study is to assess the pelvis’s morphology and spatial orientation of the acetabulum, and their relation to the severity of Congenital Femoral Deficiency (CFD) using 3D imaging. Defining these pathologies is crucial for adequate surgical correction. Methods The shape and structure of the acetabulum and pelvis were evaluated in 14 children with unilateral CFD via 3D computed tomography (CT) scans, and then analysed with geometric morphometrics (Procrustes ANOVA). The association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Radiographs can lack specificity for classifying CFD among the very young but are acceptable for initial evaluation of acetabular dysplasia. 16 CT or MRI provides more data on axial and cartilaginous acetabular morphology and can be combined with arterial mapping for preoperative planning 12,13,15,17 (Figure 3). MRIs of the knee can identify deficient cruciate ligaments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiographs can lack specificity for classifying CFD among the very young but are acceptable for initial evaluation of acetabular dysplasia. 16 CT or MRI provides more data on axial and cartilaginous acetabular morphology and can be combined with arterial mapping for preoperative planning 12,13,15,17 (Figure 3). MRIs of the knee can identify deficient cruciate ligaments.…”
Section: Discussionmentioning
confidence: 99%
“…If present, it is deficient posteriorly and laterally, leading to relative retroversion of the dome and may be globally smaller than the contralateral side. 12,13…”
Section: Acetabulummentioning
confidence: 99%
See 1 more Smart Citation
“…In a 3-dimensional anatomical study of the pelvis and acetabulum in congenital femoral deficiency, Musielak et al quantified the anatomic distortion in many ways, concluding that there is not simply a posterolateral wall deficit, but frequently a complete malorientation of the acetabular axis, perhaps suggesting that reorienting osteotomies are preferable to acetabuloplasty 22 .…”
Section: Congenital Limb Deficienciesmentioning
confidence: 99%
“…Reconstruction of acetabular dysplasia in CFD needs to take into consideration studies regarding acetabular morphology, such as research by Dora et al or Musielak et al who have demonstrated that the acetabulum in CFD is different from those of patients with developmental dysplasia of the hip and smaller, posteriorly reversed, and more inclined than those in healthy hips [17,18]. Currently used methods of acetabular reconstruction, that try to address those issues, are based on Dega or modified Dega osteotomies [2,19,20].…”
Section: Introductionmentioning
confidence: 99%